2018
DOI: 10.3390/f9110674
|View full text |Cite
|
Sign up to set email alerts
|

Tree-Ring-Recorded Drought Variability in the Northern Daxing’anling Mountains of Northeastern China

Abstract: We developed two tree-ring width chronologies of Mongolian Scots pine (Pinus sylvestris var. mongolica) from the low elevation forest of the northern Daxing’anling Mountains of Inner Mongolia. Although the two chronologies come from different sampling sites, significant correlations existed among the chronologies (r = 0.318), and the first principal component (PC1) accounted for 65.9% of total variance over their common period 1792–2016. Climate-growth correlation analysis revealed that the previous June and J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Based on the correlations between TRW indices and climatic factors, the total precipitation from previous October to current June played a key role in regulating the radial growth of Korean pine in our study area, which indicated that the total precipitation during periods before and during the early growing season is the major factor affecting the growth of Korean pine. Similar results about the climate-tree growth relationship were found in Northeast China (Chen et al, 2012;Liu et al, 2010;Yu et al, 2018a;Zhang et al, 2014;Wang and Lv, 2012) and other regions, especially in semi-arid Northwest China (Fang et al, 2013;Liang et al, 2009). We speculate that one reason is the snow accumulated early in the season, which can insulate the soil and contribute to keeping warm soil temperatures in winter and rapid water absorption by the roots in the following spring and early growing season (Fritts, 1976).…”
Section: Responses Of Radial Growth To Climatesupporting
confidence: 75%
“…Based on the correlations between TRW indices and climatic factors, the total precipitation from previous October to current June played a key role in regulating the radial growth of Korean pine in our study area, which indicated that the total precipitation during periods before and during the early growing season is the major factor affecting the growth of Korean pine. Similar results about the climate-tree growth relationship were found in Northeast China (Chen et al, 2012;Liu et al, 2010;Yu et al, 2018a;Zhang et al, 2014;Wang and Lv, 2012) and other regions, especially in semi-arid Northwest China (Fang et al, 2013;Liang et al, 2009). We speculate that one reason is the snow accumulated early in the season, which can insulate the soil and contribute to keeping warm soil temperatures in winter and rapid water absorption by the roots in the following spring and early growing season (Fritts, 1976).…”
Section: Responses Of Radial Growth To Climatesupporting
confidence: 75%
“…Our reconstruction also captured a range of changes in climate mentioned in other studies (Ahmad et al, 2004;Yu et al, 2014;Chen et al, 2019;Gaire et al, 2019). Our reconstruction featured nine dry periods (1593-1598, 1602-1608, 1631-1645, 1647-1660, 1756-1765, 1785-1800, 1870-1878, 1917-1923, and 1981-1995) and eight wet periods (1663-1675, 1687-1708, 1771-1773, 1806-1814, 1844-1852, 1932-1935, 1965-1969, and 1990-1999).…”
Section: Drought Variation In the Hindu Kush Range Of Pakistanmentioning
confidence: 75%
“…Sigdel and Ikeda (2010) reported that droughts occurred in 1974, 1977, 1985, 1993, the winter of 2001, and the summers of 1977, 1982, 1991, and 1992. Our PDSI reconstruction fully captured the widespread drought in Pakistan, Afghanistan, and Tajikistan during 1970-1971(Yu et al, 2014. The above drought disrupted daily life and led to food and water shortages and livestock losses in high-altitude areas (Yadav, 2011;Yadav and Bhutiyani, 2013;Yadav et al, 2017).…”
Section: Drought Variation In the Hindu Kush Range Of Pakistanmentioning
confidence: 88%
See 1 more Smart Citation
“…Numerous studies have shown that the intensity and frequency of drought events have increased due to rapid climate warming (Stocker et al, 2013;IPCC, 2013). The apparent drought has had serious adverse effects on social, natural, and economic systems (Ficklin et al, 2015;Yu et al, 2018;Yao et al, 2015). Global drought is considered to be the most destructive climate disaster that has caused billions of dollars in worldwide loss (Zhu et al, 2009;Seneviratne et al, 2012).…”
Section: Introductionmentioning
confidence: 99%